Trabalho docente precário: narrativas de professoras-monitoras de uma escola estadual do 1º ao 5º ano no município de Maceió-AL - Oliveira, Manuella Souza de (2015)
This text deals with the proletarization and the precariousness of the teaching profession in the context of neo-liberal policies of the State of Alagoas, adopted by the state government. Focusing on the figure of the monitors in the early years of Fundamental Education I. The monitors are teachers who work in the state of Alagoas public schools at all educational levels, whose hiring is done on a temporary basis, in order to address the lack of teachers. Our main goal was to analyze how this type of contract can affect the performance of these professional school, a dimension in the classroom. This expedient of hiring monitors has been accelerating in recent years in the State of Alagoas. The state government promoted the selection of these monitors through a notice. The methodology adopted is qualitative approach, using the narratives of life. The methodological course took place in two stages: a literature review and data collection via field research through interviews; processing and analysis of data. The research brought us to understand how this faculty hiring so tends to promote precarious processes and proletarization of these professionals, affecting the quality of education in state public schools. Teacher proletarization processes are those that hire and remunerate in a manner inconsistent with the professional status and the quality of life of individuals, especially those with higher education. The precarious process of teaching refers to the institutional conditions unfit for that professionals can do their work with quality and dignity. Alagoas is notoriously a state that has yet to improve illiteracy rates and neither has managed to universalize public school for all children. Government to use teaching strategies by hiring monitors, as of neoliberal policies, does not seem to indicate a solid via qualitative solution of these problems, making the educational situation increasingly serious.